CORRELATION BETWEEN BIRTH WEIGHT AND STUNTING IN CHILDREN UNDER FIVE A CASE-CONTROL STUDY - Tecky Afifah Santy Amartha (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2023)
Stunting is a condition in which children experience delayed growth and development due to poor nutrition, recurrent infections, and inadequate psychosocial stimulation. The prevalence of children under 5 affected by stunting in 2020 is 22.3% or 148.1 million children worldwide. The analytical case-control study was conducted to explore the prevalence of child stunting and determine the association between birth weight and stunting occurrence among children under 5 years. It shows statistically significant with a p-value of 0.009 (p-value 0.05). A history of birth weight 2500 gr babies have a 3,660 times greater risk of experiencing stunting compared to children under 5 who were born with birth weight ≥2500 gr (CI=95%). There was a significant association between birth weight and stunting incidence among children under 5 years.